On the Relevance of Freedom and Entitlement in Development : New Empirical Evidence (1975–2007) - Chauffour, Jean-Pierre (2012)
Reviewing the economic performance -- good and bad -- of more than 100 countries over the past 30 years, this paper finds new empirical evidence supporting the idea that economic freedom and civil and political liberties are the root causes of why some countries achieve and sustain better economic outcomes. For instance, a one unit change in the initial level of economic freedom between two countries (on a scale of 1 to 10) is associated with an almost 1 percentage point differential in their average long-run economic growth rates. In the case of civil and political liberties, the long-term effect is also positive and significant with a differential of 0.3 percentage point. In addition to the initial conditions, the expansion of freedom conditions over time (economic, civil, and political) also positively influences long-run economic growth. In contrast, no evidence was found that the initial level of entitlement rights or their change over time had any significant effects on long-term per capita income, except for a negative effect in some specifications of the model. These results tend to support earlier findings that beyond core functions of government responsibility -- including the protection of liberty itself -- the expansion of the state to provide for various entitlements, including so-called economic, social, and cultural rights, may not make people richer in the long run and may even make them poorer.